On application of WEB-GIS technologies in environmental screening of territories - Letyagina, E A (Journal of physics. Conference series, 2022)
This article discusses application of WEB-GIS technologies during environmental screening of territories of the Russian Federation, raising questions about the essence of the concepts of “GIS” and “WEB-GIS technologies”, and the understanding of the content aspect of these terms. Moreover, the possibility of using WEB-GIS technologies in conducting environmental monitoring is considered in sufficient detail, and the potential of these systems for the state bodies’ exercising control over the state of the environment is revealed. The article provides illustrative examples of application of WEB-GIS technologies in the implementation of environmental screening in the Krasnoyarsk Territory, a subject of the Russian Federation. In addition, the factual data – publicly available at any time through the Internet both in retrospect and by specific monitoring parameters at a particular point tied to an exact location – are analyzed. The study also identifies specific positive aspects of the use of corresponding GIS by state authorities in monitoring the state of the biosphere and tracking local environmental problems for making appropriate regulatory decisions that ensure the safety of life of the population. Furthermore, the authors identify trends, directions of development, and prospects for further use of WEB-GIS technologies during environmental screening in the territories of the Russian Federation.